Terahertz waves for contactless control and imaging in aeronautics industry. (September 2021) - Chopard, A.; Cassar, Q.; Bou-Sleiman, J.; Guillet, J.P.; Pan, M.; Perraud, J.B.; Susset, A.; Mounaix, P.
Abstract: The usability of terahertz systems for specific inspection tasks and imaging in the aeronautics industry is assessed. Especially, we demonstrate the suitability of Frequency-modulated continuous-wave (FMCW) radars for health monitoring and see-through imaging. Additionally, terahertz time-domain data processing is performed for multi-layered paint structure characterization. FMCW radar principles are introduced. Available systems are described along with their benefits and limitations. Defect detection capabilities and progresses towards airplane covering see-through imaging are illustrated through FMCW experimental results on real samples. The suitability of FMCW radars as an advanced contactless non-destructive testing (NDT) tool for the aeronautics industry and maintenance services is demonstrated. A second application, based on terahertz time domain techniques, targets the characterisation of multi-layered painting structures through the assessment of dielectric properties and individual thickness of each layer deposited. Beside the review of extraction methods, the introduced new algorithm allows to derive a parametric transfer function, thus denoting the main contributions which give rise to the recorded terahertz electromagnetic field. Such a development pushes further the understanding and characterization of stratified structures by means of terahertz radiations and represents an indispensable tool to efficiently localise any deviation to the nominal painting stack in terms of thickness or dielectric properties.